2019
DOI: 10.1177/1533033819851520
|View full text |Cite
|
Sign up to set email alerts
|

Technical Assessment of an Automated Treatment Planning on Dose Escalation of Pancreas Stereotactic Body Radiotherapy

Abstract: Background: Stereotactic body radiotherapy has been suggested to provide high rates of local control for locally advanced pancreatic cancer. However, the close proximity of highly radiosensitive normal tissues usually causes the labor-intensive planning process and may impede further escalation of the prescription dose. Purpose: The present study aims to evaluate the consistency and efficiency of Pinnacle Auto-Planning for pancreas stereotactic body radiotherapy with original prescription and escalated prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…31 A recent paper addressed the feasibility of automated planning for pancreas SBRT using step-andshoot IMRT technique. 32 The authors reported that, also in this complex anatomical site, all plans met institutional dose constraints for OARs resulting in acceptable planning target volume coverage for all targets with different prescription levels. Based on the aforementioned studies, we applied the Pinnacle Autoplanning engine to the challenging planning optimization of SBRT treatments using SIB strategy for pancreatic cancer.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…31 A recent paper addressed the feasibility of automated planning for pancreas SBRT using step-andshoot IMRT technique. 32 The authors reported that, also in this complex anatomical site, all plans met institutional dose constraints for OARs resulting in acceptable planning target volume coverage for all targets with different prescription levels. Based on the aforementioned studies, we applied the Pinnacle Autoplanning engine to the challenging planning optimization of SBRT treatments using SIB strategy for pancreatic cancer.…”
Section: Resultsmentioning
confidence: 88%
“…In particular, in our clinic, we demonstrated that the implementation of Autoplanning for complex cancer cases planned with SIB strategy as head‐neck and high‐risk prostate cancers translated into a significant increase in dose conformity and reduction in integral dose 31 . A recent paper addressed the feasibility of automated planning for pancreas SBRT using step‐and‐shoot IMRT technique 32 . The authors reported that, also in this complex anatomical site, all plans met institutional dose constraints for OARs resulting in acceptable planning target volume coverage for all targets with different prescription levels.…”
Section: Discussionmentioning
confidence: 91%
“…With such automation, human planners can be spared from many manual processes and therefore afforded more time to focus on further improving the plan quality. Wang et al ’s study 2 shows such an example in which a commercial ARIR algorithm, Pinnacle AutoPlan, was used to explore the dose-escalation limit of pancreatic stereotactic body radiotherapy (SBRT). Stereotactic body radiotherapy is an important treatment modality for borderline resectable and locally advanced pancreatic cancer that has shown promise but can be limited by normal tissue toxicity.…”
mentioning
confidence: 99%